An autosomal recessive nonsyndromic form of sensorineural hearing loss maps to 3p-DFNB6. - Fukushima, K; Ramesh, A; Srisailapathy, C R; Ni, L; Wayne, S; O'Neill, M E; Van Camp, G; Coucke, P; Jain, P; Wilcox, E R (Genome Research, 1995)
Autosomal recessive nonsyndromic hearing loss (ARNSHL) is the most common form of congenitally acquired inherited hearing impairment. Although numerous loci are believed to exist, only five have been identified. Using a pooled genomic DNA screening strategy, we have identified a sixth locus, DFNB6, on 3p in the interval bounded by D3S1619 and D3S1766.